2014
DOI: 10.1186/1471-2407-14-808
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq profiling of a radiation resistant and radiation sensitive prostate cancer cell line highlights opposing regulation of DNA repair and targets for radiosensitization

Abstract: BackgroundRadiotherapy is a chosen treatment option for prostate cancer patients and while some tumours respond well, up to 50% of patients may experience tumour recurrence. Identification of functionally relevant predictive biomarkers for radioresponse in prostate cancer would enable radioresistant patients to be directed to more appropriate treatment options, avoiding the side-effects of radiotherapy.MethodsUsing an in vitro model to screen for novel biomarkers of radioresistance, transcriptome analysis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
(51 reference statements)
3
33
0
1
Order By: Relevance
“…To investigate the association between miR-21 expression and radiation sensitivity, a radiation-resistant non-small cell lung cancer cell line was generated using A549 parental cells, according to a previous study (22). The cells were treated with increasing doses of radiation for 4 months, in order to generate resistant cells.…”
Section: Mir-21 Expression Levels Are Higher In Radiation-resistant Lmentioning
confidence: 99%
“…To investigate the association between miR-21 expression and radiation sensitivity, a radiation-resistant non-small cell lung cancer cell line was generated using A549 parental cells, according to a previous study (22). The cells were treated with increasing doses of radiation for 4 months, in order to generate resistant cells.…”
Section: Mir-21 Expression Levels Are Higher In Radiation-resistant Lmentioning
confidence: 99%
“…Several reports suggest that radioresistance is associated with the enhanced repair of radiation-induced DNA damage [1] [7] [18] [19]. Our previous study also showed that X-ray-induced phosphorylated histone H2AX (γH2AX) foci disappear more rapidly in HepG2-8960-R than in parental HepG2 [1].…”
Section: Introductionmentioning
confidence: 75%
“…(25) Alternatively, SNPs in other DNA-repair genes have also been associated with an increased risk of radiation-induced toxicity in patients treated for prostate cancer. (26) However, few studies have evaluated radiosensitivity and survival outcomes in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%